2010
DOI: 10.1143/jjap.49.07hc11
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Imaging of Nonmetallic Inclusions in Continuously Cast Steel Plates by Higher Harmonics

Abstract: We study the level spacing distribution p(s) in the spectrum of random networks. According to our numerical results, the shape of p(s) in the Erdős-Rényi (E-R) random graph is determined by the average degree k and p(s) undergoes a dramatic change when k is varied around the critical point of the percolation transition, k = 1. When k 1, the p(s) is described by the statistics of the Gaussian orthogonal ensemble (GOE), one of the major statistical ensembles in Random Matrix Theory, whereas at k = 1 it follows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In 1998, Nagy et al [12] used nonlinear ultrasonic tests to evaluate the performance degradation of materials from cracks to fractures and predict the fatigue life of the materials. In 2010, Kawashima [13] used a nonlinear scanning system to detect non-metallic inclusions in continuum cast steel. In 2011, Viswanath [14] found that nonlinear coefficients can be used to characterize the degradation of mechanical properties of materials under tensile loads.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Nagy et al [12] used nonlinear ultrasonic tests to evaluate the performance degradation of materials from cracks to fractures and predict the fatigue life of the materials. In 2010, Kawashima [13] used a nonlinear scanning system to detect non-metallic inclusions in continuum cast steel. In 2011, Viswanath [14] found that nonlinear coefficients can be used to characterize the degradation of mechanical properties of materials under tensile loads.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Jhang and Kim [7] researched the relationship between the mechanical properties degradation of the material and the nonlinearity parameter under tensile load. In 2010, Kawashima et al [8] detected the nonmetallic inclusions in the continuous casting steels using a nonlinear scanning system. In 2012, Cremer et al [9] carried out the in situ observation of the very high cycle fatigue damage evolution of aluminum alloy welded joints using nonlinear ultrasonic technology.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound waves attenuate inside a metal because of diffusion and grain boundary scattering. [14][15][16][17] Although the pulse echo method is useful for forge steel, which is comparatively low-attenuation steel, it is not effective for high-attenuation steel such as cast steel. 18) Therefore, an ultrasonic transmission method is expected to detect defects inside high-attenuation billets.…”
Section: Introductionmentioning
confidence: 99%